Exploration of the relationship between the Manual Ability Classification System and hand-function measures of capacity and performance. (June 2013) - Öhrvall, Ann-Marie; Krumlinde-Sundholm, Lena; Eliasson, Ann-Christin
<x xml:space="preserve">Abstract</x> Purpose: To further investigate the construct of Manual Ability Classification System (MACS) by evaluating the relationship between children's designated MACS levels and their outcomes on two different tests of hand function, measuring capacity and performance, respectively. Another aim was to use the International Classification of Functioning, Disability and Health-Child and Youth version (ICF-CY) as a framework to explore the uniqueness of the assessments. Method: Ninety-one children with cerebral palsy in MACS levels I–V, aged 5–17 years (mean 9.8, SD 3.0) participated. Data were collected using MACS, ABILHAND-Kids and Box and Block Test. Results: A strong association between MACS and ABILHAND-Kids (rs = −0.88, p < 0.05) and MACS and Box and Block Test (rs = −0.81, p < 0.05) was demonstrated. Children's performance differed significantly between the different MACS levels (ABILHAND-Kids F (4:86) = 103.86, p < 0.001, Box and Block Test F (4:86) = 59.18, p < 0.001). The content comparison with ICF-CY, as a frame of reference, showed that these instruments capture fine hand use in the activity and participation component. The linking of the instruments to various ICF-CY categories demonstrated conceptual differences between the instruments. MACS had the broadest representation of ICF-CY domains. Conclusions: This study strengthens the construct, and thereby the validity, of MACS as a classification of children's hand function, expressed by the handling of objects in everyday activities in their daily environments.